Filling Gap in EFL Teachers' Informal Formative Assessment: Insights from Higher Education Level - Milawati, Milawati; Suryati, Nunung; Rohmah, Dewi Wardah Mazidatur (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
This study presents the informal formative assessment practice embedded in teacher-students interaction in daily teaching activities. Although many previous studies claimed as informal formative assessment, the adequate information on how informal formative assessment integrated in EFL classroom interaction in the higher education level was not acquired yet. A case study design on ESRU Model was used with 59 Indonesian EFL teachers in higher education level. Online Survey questionnaire was used to determine participants to be involved for further investigation in classroom observation and interview. This research highlighted clarifying learning goal as prerequisite activity before conducting the ESRU model activities. Interestingly, of the four activities in ESRU model, the use information gained was potentially support students’ learning compared to other three activities; Elicits information, the student responds, and the teacher recognizes students’ responses. Hence, this study can contribute insight for the teachers to reflect their own teaching practice.